A SEGURANÇA DAS FAMILlAS NOS PROGRAMAS SOCIAIS BRASILEIROS E O SISTEMA DE INFORMAÇÃO DE GESTÃO SOCIAL-SIGS - Ana Rojas Acosta (Universidade Federal do Maranhão, 2012)
It is indisputable progress in the Brazilian social policies from the 1988 Federal Constitution upon the approval of social security policy as a social policy that aims to provide security lo lhe society Itlrough lhe tripod (pension, health and social care). The social programs implemented afterlhis Conslilution look different directions and need lo be evaluated for their effectiveness, efficiency and effectiveness. ln this sense, moniloring and evalualion of these programs are essential and lhe infonnation syslem of social managemenl proposes lo conlribute to the Nalional Social Policy as an inslrumenl of social management.